Reading the “power of clothes” in the Deuteronomic Code - Dr Doniwen Pietersen (Africajournals, 2021)
This article explores the ancient Israelite law, namely the Deuteronomic Code (Deut. 12–26), in terms of how men and women were treated differently when it came to cultural adornment practices. In other words, the Deuteronomic Code was used culturally to hold women back and treated them differently in ancient Israel. It enforced the degradation of women. The legal terminology used when dealing with women and their cultural adornment practices is out of place when it comes to gender. The following areas are addressed in this work: How were anti-women practices enmeshed in the Israelite legal system (Deuteronomic Code)? Were these law codes resistant or open to change in the course of her history? In answering these questions, a feminist approach found that Israel did indeed subordinate and forcefully disenfranchise women.